REFLEXIVELY MASSAGE IN SLEEP EFFICIENCY - Pasăre Daniela; Raţă Elena (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
This article presents a study that is based on questioning and observing certain categories of respondents directly involved with the research subject namely to establish conclusive elements and the possibilities of generalization in the composition and content of the schemes used in the application of manual therapy (massage reflex disorders) in the recovery of people suffering from sleeplessness due to daily stress, depression or other causes.